PENINGKATAN HASIL BELAJAR MATEMATIKA MATERI PERKALIAN DENGAN PENERAPAN MEDIA PEMBELAJARAN BATANG NAPIER PESERTA DIDIK KELAS IV SDN LIDAH WETAN IV/566 SURABAYA - Sariningsih, Fitri Eka; Suprayitno; Arfiani Ika Nuraini (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
The aim of this research is to examine whether the application of  Napier stem can improve the learning outcomes of class IV students at SDN Lidah Wetan IV/566 Surabaya. This research used collaborative Classroom Action Research (PTK) techniques, with 10 class IV students as research subjects. This research focuses on student learning outcomes in multiplication, with data collected through assessments and studied descriptively and quantitatively. The results of cycle I showed an average score of 69, with the lowest score being 55 and the highest score being 80, and 50% of students met the Minimum Completeness Criteria (KKM). In cycle II, the average score increased to 77.5, with the lowest score being 55 and the highest score being 85, and 80% of students met the Minimum Completeness Criteria (KKM). This research shows that the application of mathematics learning media in the form of Napier rods can improve student learning outcomes in the mathematics subject of multiplication material.